Perovskite solar cell modified by hydrazinobenzene phosphorous acid additive and preparation method and application thereof

By using hydrazine benzene phosphorite as an additive in perovskite solar cells, we jointly passivate the defects of the perovskite layer and inhibit lead leakage, solving the problems of long-term operation stability and lead leakage of perovskite solar cells, and achieving efficient, stable and environmentally friendly solar cell performance.

CN119894341AActive Publication Date: 2025-04-25GUANGDONG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510284824.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-25
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

Perovskite solar cells have insufficient long-term operation stability under high-efficiency conditions, and the water-soluble lead halide material is high, resulting in lead leakage and affecting environmental and biosafety.

Method used

Hydroxybenzene phosphorite is used as an additive for perovskite solar cells, and hydrogen bonds are formed with halogen ions through the coordination of the phosphate group with Pb2+ and the N-H bond in the hydrazine group, which jointly passivates the defects of the perovskite layer and inhibits the leakage of lead.

Benefits of technology

It significantly improves the photoelectric conversion efficiency and stability of perovskite solar cells, reduces lead leakage, and achieves coordinated optimization of device efficiency-life-environmentality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894341A_ABST
    Figure CN119894341A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrazinobenzene phosphorous acid additive modified perovskite solar cell and a preparation method and application thereof, and belongs to the technical field of photovoltaic solar materials. Hydrazinobenzene phosphorous acid is used as a perovskite solar cell additive, hydrazinobenzene phosphorous acid micromolecules have electron donating groups (hydrazino) and electron withdrawing groups (phosphate groups), the phosphate groups and Pb < 2 + > form coordination, N-H bonds in the hydrazino and halogen ions form hydrogen bonds, the two groups synergistically passivate Pb < 2 + >, Pb < 0 > and halogen ion vacancies through coordination and the hydrogen bonds, and the Pb < 2 + >, Pb < 0 > and halogen ion vacancies are formed. And non-radiative recombination is obviously reduced. By balancing strong and weak interaction of covalence and non-covalence, the defects of a perovskite crystal phase are reduced, perovskite crystals are induced to grow better, carrier recombination in perovskite is inhibited, and the photoelectric conversion efficiency and stability of a device are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photovoltaic solar energy materials, and in particular relates to a perovskite solar cell modified with a hydrazinophenylphosphite additive, and a preparation method and application thereof. Background Art

[0002] As the global energy structure accelerates its transition to low-carbonization, new energy technology has become the cross-focus of semiconductor material science and clean energy revolution. In the context of the deep integration of new energy and semiconductor technology, perovskite materials, as the core of the third-generation semiconductor technology, have unique organic-inorganic hybrid semiconductor properties (bandgap adjustable range 1.2 ~ 2.3eV, carrier mobility > 10cm 2 / V·s and longer exciton diffusion length), has become a research hotspot in the photovoltaic field. The new energy industry (such as solar power generation) has an increasingly urgent demand for high-efficiency and low-cost semiconductor devices. Perovskite semiconductor materials can significantly reduce the levelized cost of electricity (LCOE) of photovoltaic power generation by more than 40% by virtue of their low-temperature process (<150℃) prepared by solution method and a theoretical photoelectric conversion efficiency of up to 33% (significantly exceeding the 29.4% limit of crystalline silicon semiconductors), and are regarded as a key path to break through the bottleneck of traditional silicon-based semiconductor photovoltaic technology.

[0003] However, in the large-scale application scenarios of new energy, the bottlenecks of photoelectric conversion efficiency, stability and safety of perovskite semiconductor devices need to be broken through. Although the increasingly prominent perovskite solar cells have the advantages of excellent device performance, low device preparation cost and solution preparation, they are limited by the structure and properties of the materials. Water, oxygen, light and heat can all cause the materials to decompose. Therefore, the long-term operational stability of perovskite solar cells under high-efficiency conditions has not yet been achieved, which remains a key obstacle to overcome before full marketization. In addition, for perovskite solar cells prepared from lead halides, due to the higher water solubility of lead halides (K in rainwater), the water solubility of lead halides is relatively high. sp More than 10 -8 ). Lead leakage has serious impacts on organisms and the environment. Therefore, it is necessary to use appropriate materials to optimize the quality of perovskite films, which can effectively delay the degradation process of perovskite films, inhibit lead leakage, and improve the comprehensive performance of devices, thus achieving the coordinated optimization of efficiency, lifespan, and environmental friendliness of new energy devices.

[0004] The prior art discloses a high-efficiency tin-lead alloy perovskite solar cell prepared by using 4-hydrazinebenzoic acid as an additive, wherein 4-hydrazinebenzoic acid is used to inhibit Sn 2+ The oxidation of the perovskite can passivate the defects of the perovskite at the same time. The photoelectric conversion efficiency of the battery is 18.58% to 20.49%, and the photoelectric efficiency still needs to be improved. Summary of the invention

[0005] In order to solve the problems existing in the above-mentioned prior art, the primary purpose of the present invention is to provide the use of hydrazinophenylphosphorous acid as an additive for perovskite solar cells.

[0006] Another object of the present invention is to provide a use of hydrazinophenylphosphorous acid as an additive for a perovskite layer of a perovskite solar cell.

[0007] Another object of the present invention is to provide a perovskite solar cell.

[0008] Another object of the present invention is to provide a method for preparing a perovskite solar cell.

[0009] Another object of the present invention is to provide an application of perovskite solar cells in the preparation of photovoltaic power generation equipment.

[0010] In order to achieve the above object, the present invention provides the following technical solutions:

[0011] Application of hydrazinophenylphosphorous acid as an additive for perovskite solar cells.

[0012] Application of hydrazinophenylphosphorous acid as an additive for the perovskite layer of perovskite solar cells.

[0013] The present invention uses hydrazine phenylphosphite as a perovskite solar cell additive. The phosphoric acid in hydrazine phenylphosphite can induce grain growth, and the O=P group in the phosphoric acid group can react with Pb 2+ Coordination, thereby forming an adduct, while inducing and strengthening the interaction between adjacent perovskite crystals, making the perovskite crystal grow better, passivating the internal defects of the perovskite layer, and reducing carrier loss; the NH bond of the hydrazine group in the hydrazine phenylphosphite can form a hydrogen bond with the halogen ions in the perovskite layer, reducing iodine migration and inhibiting defect-induced non-radiative recombination, further improving the open circuit voltage of the perovskite solar cell. In the present invention, the phosphate group and the hydrazine group work synergistically, which can further improve the efficiency and stability of the solar cell.

[0014] Due to factors such as excessive addition of lead iodide in the perovskite layer and degradation of lead iodide, Pb is easily formed in the perovskite crystal. 0 defects, which can significantly increase carrier recombination and reduce device efficiency and stability. Phosphate groups can convert Pb 0 Converted to Pb 2+ and stabilizes Pb by coordination 2+ , thereby inhibiting the degradation of lead iodide, or by adsorbing and covering Pb 0 Surface, inhibiting Pb 0 become carrier recombination centers.

[0015] Phosphate group in hydrazinophenylphosphite and Pb 2+ The strong coordination effect of Pb2+ The transfer of lead ions makes it have excellent lead fixing ability, thereby inhibiting the leakage of lead ions.

[0016] A method for improving the photoelectric efficiency of a perovskite solar cell comprises adding hydrazinophenylphosphorous acid to a perovskite precursor solution.

[0017] Specifically, the concentration of hydrazinophenylphosphorous acid in the perovskite precursor solution is 0.1 to 0.3 mg / mL.

[0018] Preferably, the concentration of hydrazinophenylphosphite in the perovskite precursor solution is 0.15-0.25 mg / mL.

[0019] Specifically, the solvent of the hydrazinophenylphosphite solution is at least one of DMSO, DMF and ACN.

[0020] A perovskite solar cell additive comprises: hydrazinophenylphosphite.

[0021] A perovskite solar cell has a device structure which comprises, from bottom to top, a conductive glass layer, a hole transport layer, a perovskite layer, an electron transport layer and a metal electrode layer, wherein the perovskite layer contains hydrazinophenylphosphite.

[0022] Specifically, the conductive glass layer is one of ITO conductive glass and FTO conductive glass.

[0023] Specifically, the hole transport layer is at least one of PTAA, MeO-2PACz, and Me-2PACz.

[0024] Specifically, the perovskite layer includes formamidine hydrohalide, alkylammonium halide, cesium halide and lead halide.

[0025] More specifically, the formamidine halide salt is at least one of formamidine hydrochloride, formamidine bromide and formamidine iodide.

[0026] More specifically, the alkylammonium halide is at least one of methylammonium iodide, methylammonium chloride and methylammonium bromide.

[0027] More specifically, the cesium halide is at least one of cesium iodide, cesium chloride or cesium bromide.

[0028] More specifically, the lead halide is at least one of lead iodide, lead chloride or lead bromide.

[0029] Preferably, the perovskite layer comprises formamidine hydroiodide, methylammonium chloride, methylammonium iodide, cesium iodide and lead iodide.

[0030] Specifically, the thickness of the perovskite layer is 680-720 nm.

[0031] Specifically, the material of the electron transport layer is a carbon 60 derivative.

[0032] More specifically, the carbon 60 derivative is at least one of [6,6]-phenyl C61 butyric acid methyl ester, [6,6]-thienyl C61 butyric acid methyl ester, [6,6]-phenyl-C61-butyric acid n-octyl ester or [6,6]-phenyl-C61-butyric acid dodecyl ester.

[0033] A method for preparing a perovskite solar cell comprises: sequentially preparing a hole transport layer, a perovskite layer, an electron transport layer and a metal electrode layer on a conductive glass layer by a spin coating method, wherein the method for preparing the perovskite layer comprises the following steps:

[0034] S1. mixing hydrazinophenylphosphorous acid with the perovskite solution to obtain a first perovskite precursor solution,

[0035] S2. Spin coating the first perovskite precursor solution, heating and annealing, to obtain the perovskite layer.

[0036] Specifically, the active components in the perovskite precursor solution include formamidine hydrohalide, alkyl ammonium halide, cesium halide and lead halide.

[0037] The active components in the perovskite precursor solution are non-solvent components and do not include additives.

[0038] Preferably, the active components in the perovskite precursor solution include formamidine hydroiodide, methylammonium chloride, methylammonium iodide, cesium iodide and lead iodide.

[0039] Preferably, the chemical formula of the active component in the perovskite precursor solution is Cs x (FA y MA 1-y ) 1-x PbI3, where 0<x≤0.1, 0.5≤y<1.

[0040] Specifically, the ratio of the total mass of active components in the perovskite precursor solution to the mass of hydrazinophenylphosphorous acid is (1100-1150): (0.1-0.3).

[0041] More specifically, the ratio of the total mass of active components in the perovskite precursor solution to the mass of hydrazinophenylphosphorous acid is 1122:(0.1-0.3).

[0042] Specifically, in step S1, the mixing time is 12 to 18 hours.

[0043] Specifically, the solvent of the first perovskite precursor is at least one of DMF, DMSO and ACN.

[0044] Specifically, in step S2, the rotation speed of the spin coating is 3500-4500 rpm.

[0045] Specifically, in step S2, the spin coating time is 20 to 40 seconds.

[0046] Specifically, in step S2, the temperature of heating annealing is 80-120°C.

[0047] Specifically, in step S2, the heating annealing time is 10 to 50 minutes.

[0048] The present invention also protects the use of the above-mentioned perovskite solar cell in the preparation of photovoltaic power generation equipment.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] The present invention uses hydrazinophenylphosphite as a perovskite solar cell additive. The hydrazinophenylphosphite small molecule has an electron-donating group (hydrazino group) and an electron-withdrawing group (phosphate group). The phosphate group reacts with Pb 2+ The NH bond in the hydrazine group forms a hydrogen bond with the halogen ion. The two groups synergistically passivate Pb through coordination and hydrogen bonding. 2+ , Pb 0 The present invention reduces the defects of the perovskite crystal phase by balancing the two strong and weak interactions of covalent and non-covalent, and induces better growth of perovskite crystals, inhibits the recombination of carriers in perovskite, improves the photoelectric conversion efficiency and stability of the device, and effectively inhibits the leakage of lead ions in perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 JV curves of the perovskite solar cells of the embodiments and comparative examples.

[0052] Figure 2 This is the molecular structure of hydrazinophenylphosphite.

[0053] Figure 3 2 and 3. Steady-state photoluminescence (PL) spectra of the perovskite layers of Example 3 and Comparative Example 1.

[0054] Figure 4 Time-resolved photoluminescence (TRPL) spectra of the perovskite layers of Example 3 and Comparative Example 1.

[0055] Figure 5 The XRD diagrams of Example 3 and Comparative Example 1 are shown in FIG.

[0056] Figure 6 The UV-Vis graph (left graph) and Tauc graph (right graph) of Example 3 and Comparative Example 1 are shown.

[0057] Figure 7 The SEM images of Example 3 and Comparative Example 1 are shown.

[0058] Figure 8 It is the normalized efficiency-time curve diagram of Example 3 and Comparative Example 1.

[0059] Fig. 9 The lead leakage curve diagram of Example 3 and Comparative Example 1 and the device water immersion test diagram are shown. DETAILED DESCRIPTION

[0060] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.

[0061] A perovskite solar cell additive, the preparation method of which comprises the following steps:

[0062] 2 mg of hydrazinophenylphosphite was added to 1 mL of DMSO, and the mixture was magnetically stirred at 60° C. for 60 minutes to form a hydrazinophenylphosphite solution with a concentration of 2.0 mg / mL, thereby obtaining a perovskite solar cell additive.

[0063] The chemical formula of the active component in the perovskite precursor solution in the examples and comparative examples is Cs 0.05 (FA 0.8 MA 0.2 ) 0.95 PbI3.

[0064] Example 1

[0065] This embodiment provides a perovskite solar cell, the device structure of which is, from bottom to top, a conductive glass layer, a hole transport layer, a perovskite layer, an electron transport layer and a metal electrode layer. The preparation method thereof comprises the following steps:

[0066] S1. The ITO conductive glass was ultrasonically cleaned in deionized water, acetone and isopropanol for 15 minutes in sequence, dried with nitrogen, and placed in a UV-ozone cleaning machine for UV-ozone treatment; after cleaning, it was quickly transferred to a nitrogen atmosphere glove box, and then the hole transport layer PTAA was spin-coated on the ITO substrate. The spin coating speed was set to 3000 rpm and the spin coating time was 30 seconds. After 25 seconds, 20 microliters of PTAA was added dropwise on the ITO substrate. After the spin coating was completed, it was transferred to a heating table and heated at 100°C for 10 minutes to obtain a hole transport layer;

[0067] S2.1 Dissolve formamidine hydroiodide, methylammonium chloride, methylammonium iodide, cesium iodide and lead iodide in DMF and DMSO, add 0.05 ml of 2.0 mg / ml hydrazinophenylphosphite solution (i.e., perovskite solar cell additive), and stir magnetically for 15 hours to obtain a perovskite precursor solution; the concentration of hydrazinophenylphosphite in the perovskite precursor solution is 0.1 mg / mL; the ratio of the total mass of active components in the perovskite precursor solution to the mass of hydrazinophenylphosphite is 1122:0.1.

[0068] S2.2 dripping the perovskite precursor solution onto the PTAA-modified ITO substrate, setting the spin coating speed to 4000 rpm, the spin coating time to 35 seconds, and dripping the anti-solvent toluene at 10 seconds, then transferring to a heating table for heating annealing at 100°C for 30 minutes, forming a perovskite film on the PTAA-modified ITO substrate to obtain a perovskite layer;

[0069] S3. 23 mg of [6,6]-phenyl C 61 Methyl butyrate was dissolved in 1 ml of chlorobenzene and stirred for 15 hours to prepare PC 61 BM electron transport layer solution, PC 61 The BM electron transport layer solution was dropped onto the perovskite layer and spin-coated to form the PC 61 BM film, set the spin coating speed to 3000rpm, the spin coating time to 30 seconds, transfer to the heating table after the spin coating is completed, and heat at 100℃ for 10 minutes; 2.5mg of bathocuproin BCP was dissolved in 1ml of isopropanol and stirred for 15 hours to prepare a BCP solution, and the BCP solution was added dropwise to the PC 61 Static spin coating was performed on the BM film, with the spin coating speed set to 3000 rpm and the spin coating time set to 30 seconds to obtain an electron transport layer;

[0070] S4. Place the device prepared in step S3 into a vacuum coating machine, evacuate the vacuum, then place a silver metal source into a tungsten boat, evaporate a silver electrode, and obtain a metal electrode layer; after assembly, a perovskite solar cell is obtained.

[0071] Example 2

[0072] The difference between this embodiment and embodiment 1 is that: in step S2.1, 0.075 ml of a 2.0 mg / ml hydrazinophenylphosphite solution is added, and the concentration of hydrazinophenylphosphite in the perovskite precursor solution is 0.15 mg / mL; the ratio of the total mass of active components in the perovskite precursor solution to the mass of hydrazinophenylphosphite is 1122:0.15.

[0073] Example 3

[0074] The difference between this embodiment and embodiment 1 is that: in step S2.1, 0.10 ml of a 2.0 mg / ml hydrazinophenylphosphite solution is added, and the concentration of hydrazinophenylphosphite in the perovskite precursor solution is 0.2 mg / mL; the ratio of the total mass of active components in the perovskite precursor solution to the mass of hydrazinophenylphosphite is 1122:0.2.

[0075] Example 4

[0076] The difference between this embodiment and embodiment 1 is that: in step S2.1, 0.125 ml of a 2.0 mg / ml hydrazinophenylphosphite solution is added, and the concentration of hydrazinophenylphosphite in the perovskite precursor solution is 0.25 mg / mL; the ratio of the total mass of active components in the perovskite precursor solution to the mass of hydrazinophenylphosphite is 1122:0.25.

[0077] Example 5

[0078] The difference between this embodiment and embodiment 1 is that: in step S2.1, 0.15 ml of a 2.0 mg / ml hydrazinophenylphosphite solution is added, and the concentration of hydrazinophenylphosphite in the perovskite precursor solution is 0.3 mg / mL; the ratio of the total mass of active components in the perovskite precursor solution to the mass of hydrazinophenylphosphite is 1122:0.3.

[0079] Comparative Example 1

[0080] The difference between this comparative example and Example 1 is that no hydrazinophenylphosphite is added to the first perovskite precursor solution, and the rest is the same as Example 1.

[0081] Comparative Example 2

[0082] The difference between this comparative example and Example 1 is that hydrazinophenylphosphorous acid is replaced by hydrazinobenzoic acid.

[0083] Comparative Example 3

[0084] The difference between this comparative example and Example 3 is that hydrazinophenylphosphorous acid is replaced by hydrazinophenylphosphoric acid hydrochloride.

[0085] Performance Testing

[0086] Current density-voltage (JV) characteristic curve test: The performance of the device is evaluated by measuring the JV characteristic curve. The experiment uses a solar simulator to provide AM 1.5G, 100mW·cm -2 The JV characteristic curve can be obtained by applying bias voltage to both ends of the test battery and measuring the current of its external circuit using a Keithley 2400C digital source meter. The effective area of ​​the device is 0.04cm 2 .

[0087] Steady-state fluorescence emission (PL) spectral characterization test: Fluorescence emission characterization uses quartz or glass as the substrate to prepare the sample. The test sample is spin-coated with a perovskite layer on a transparent conductive glass to prepare a complete sample. When testing steady-state PL, a xenon lamp is used as the excitation light source. When testing transient PL, another excitation light source is used. When fitting the transient PL lifetime, a double exponential fitting method is used, and it is ensured that the fitting exponent χ 2 is approximately 1 to ensure the reliability of the fitting.

[0088] X-ray diffraction (XRD) characterization test: Fluorescence emission characterization uses quartz or glass as a substrate to prepare samples. The test sample is coated with a hole transport layer on a transparent conductive glass, and then the perovskite layer is spin-coated to prepare a complete sample. The scanning angle is 10-45°. The effect of hydrazine phenylphosphite on the crystallinity of perovskite film is studied.

[0089] Ultraviolet absorption (UV-Vis) spectroscopy characterization test: Fluorescence emission characterization uses quartz or glass as a substrate to prepare samples. The test sample is spin-coated with a perovskite layer on a transparent conductive glass to prepare a complete sample. The scanning range is 300-800nm. The effect of hydrazine phenylphosphite on the optoelectronic properties of perovskite films is studied.

[0090] Field emission electron scanning (SEM) microscope characterization test: Fluorescence emission characterization uses quartz or glass as a substrate to prepare samples. The test sample is coated with a hole transport layer on a transparent conductive glass, and then the perovskite layer is spin-coated and annealed to prepare a complete sample. The cross-sectional sample is a quartz or glass sample cut from the smooth back with a glass knife to obtain a flat sample.

[0091] Normalized efficiency-time curve test: The unpackaged and complete perovskite solar photovoltaic device was placed in a glove box with a nitrogen atmosphere at room temperature (25±2°C) and the JV device test was completed regularly.

[0092] Device immersion test: Place the unpackaged and complete perovskite solar photovoltaic device in 50ml of distilled water at 25℃, then take 2.5ml of water as sample at regular intervals, and use the atomic flame absorption (FAAs) method to quantitatively analyze the content of lead in the water by measuring the degree of absorption of characteristic light by the lead atomic vapor in the sample.

[0093] The experimental results are as follows:

[0094] Figure 1 The JV curves of the perovskite solar cells of the embodiment and the comparative example are shown in Table 1.

[0095] Table 1 JV test results of perovskite solar cells of the embodiment and comparative example

[0096]

[0097] As can be seen from Table 1, the photoelectric conversion efficiency of the perovskite solar device using hydrazinophenylphosphite as a perovskite solar cell additive is generally better than that of the perovskite solar device without the additive (i.e., Comparative Example 1) and the perovskite solar device using hydrazinobenzoic acid additive (i.e., Comparative Example 2), indicating that hydrazinophenylphosphite has a significant effect on improving the efficiency of the perovskite device.

[0098] It can be seen from Example 1 and Comparative Example 2 that the photoelectric conversion efficiency of the perovskite solar cell of Comparative Example 2 is lower than that of Example 1. This indicates that the passivation effect of the phosphate group in hydrazinophenylphosphorous acid on the perovskite layer is much stronger than the passivation effect of the carboxyl group in hydrazinobenzoic acid on the perovskite layer.

[0099] It can be seen from Example 3 and Comparative Example 3 that the photoelectric conversion efficiency of the perovskite solar cell in Comparative Example 3 is lower than that in Example 3. This shows that the passivation effect of the phosphate group in hydrazine phenylphosphorous acid on the perovskite layer is much stronger than that of hydrazine phenylphosphoric acid hydrochloride on the perovskite layer. This is because pure hydrazine phenylphosphorous acid does not contain Cl - Its phenylphosphate group binds to Pb through the phosphate group 2+ coordination, forming more uniform nucleation sites and promoting the formation of dense, large-grained perovskite films. - The introduction of Cl will prolong the nucleation time of perovskite, resulting in uneven grain size distribution and increased grain boundary defect density. - It is difficult to completely volatilize during annealing, and the unvolatile Cl - It may remain at the grain boundary or in the lattice, forming ion migration channels or recombination centers, reducing device efficiency. - with I - The size difference may lead to lattice mismatch, Cl - The introduction of may weaken the hydrogen bond network and reduce the passivation effect.

[0100] Figure 3 The steady-state photoluminescence (PL) spectra of the perovskite layer of Example 3 and Comparative Example 1 show that the fluorescence peak luminescence intensity of Example 3 is stronger than that of Comparative Example 1, indicating that the perovskite film with the addition of hydrazinophenylphosphite generates more carriers by photoexcitation, which can effectively reduce the non-radiative recombination caused by defects in the perovskite layer. Figure 43 and 1. The time-resolved photoluminescence (TRPL) spectra of the perovskite layer of Example 3 and Comparative Example 1 show that the fluorescence lifetime curve of the perovskite intrinsic layer of Example 3 is higher than that of Comparative Example 1, indicating that the lifetime of the perovskite film in Example 3 is extended. This is because hydrazinophenylphosphite as an additive for perovskite solar cells can reduce grain boundary defects, has a better defect passivation effect, and can effectively reduce the non-radiative recombination and loss of photogenerated carriers at defects.

[0101] Figure 5 3 and Comparative Example 1, in which the diffraction peaks at 12.7° and 14.4° respectively represent the unreacted lead iodide and (110) crystal plane of the perovskite. As can be seen from the figure, the diffraction angle of Example 3 did not change significantly, indicating that the hydrazinophenylphosphite did not change the perovskite structure. The perovskite modified with the hydrazinophenylphosphite additive has almost no diffraction peak of lead iodide, indicating that the lead iodide is almost completely converted into perovskite. Compared with Comparative Example 1, the diffraction peak intensity corresponding to the (110) crystal plane of Example 3 increases, which indicates that the hydrazinophenylphosphite additive enhances the crystallization quality of the perovskite film.

[0102] Figure 6 The UV-Vis graph (left graph) and Tauc graph (right graph) of Example 3 and Comparative Example 1 show that Example 3 shows a slight blue shift compared to Comparative Example 1. The band gap of the perovskite film obtained from the Tauc graph obtained from the ultraviolet absorption spectrum also shows that the band gap E of the perovskite layer of Example 3 and Comparative Example 1 is g The band gap did not change significantly, which means that the hydrazine phenylphosphine additive did not significantly change the lattice constant of the material, nor did it change the composition ratio of the perovskite layer.

[0103] Figure 7 The SEM images of Example 3 and Comparative Example 1 show that the grain size of the perovskite intrinsic layer with the addition of hydrazinophenylphosphite has increased significantly, and the size is relatively uniform. Compared with Comparative Example 1 without the addition of hydrazinophenylphosphite, Example 1 has larger and more homogeneous grains, which can improve the open circuit voltage of the device. In addition, from the cross-sectional view, it can be seen that the perovskite layer Example 3 with the addition of hydrazinophenylphosphite and the perovskite layer Comparative Example 1 without the addition of materials have almost no change in the thickness of the perovskite film, both of which are 680 to 720 nm, and the grains of the perovskite layer with the addition of hydrazinophenylphosphite are more neat, indicating that the perovskite crystal quality of Example 3 is better than that of Comparative Example 1.

[0104] Figure 8The normalized efficiency-time curves of Example 3 and Comparative Example 1 show that the perovskite solar cell modified with hydrazinophenylphosphite additive exhibits excellent stability. After aging for 4800 hours in a nitrogen atmosphere, the device efficiency can still maintain 90.2% of the initial efficiency, which is much better than Comparative Example 1 without adding hydrazinophenylphosphite.

[0105] Fig. 9 The lead leakage content diagram of Example 3 and Comparative Example 1 and the device immersion test diagram show that after 200 minutes, the lead leakage of Example 3 is much smaller than that of Comparative Example 1, which proves that the hydrazinophenylphosphite additive has a strong lead fixing ability in the perovskite material and inhibits the leakage of lead ions in the perovskite.

[0106] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. Application of hydrazinophenylphosphorous acid as an additive for perovskite solar cells.

2. Application of hydrazinophenylphosphorous acid as an additive for the perovskite layer of perovskite solar cells.

3. A method for improving the photoelectric efficiency of a perovskite solar cell, characterized in that: In the perovskite precursor solution, hydrazinophenylphosphite is added.

4. The method according to claim 3, characterized in that: The concentration of hydrazinophenylphosphite in the perovskite precursor solution is 0.1-0.3 mg / mL.

5. A perovskite solar cell, wherein the device structure is, from bottom to top, a conductive glass layer, a hole transport layer, a perovskite layer, an electron transport layer and a metal electrode layer, characterized in that: The perovskite layer contains hydrazinophenylphosphorous acid.

6. The perovskite solar cell according to claim 5, characterized in that: The thickness of the perovskite layer is 680-720 nm.

7. A method for preparing a perovskite solar cell according to claim 5 or 6, comprising: A hole transport layer, a perovskite layer, an electron transport layer and a metal electrode layer are sequentially prepared on a conductive glass layer by a spin coating method, wherein the preparation method of the perovskite layer comprises the following steps: S1. Mixing hydrazinophenylphosphorous acid with the perovskite solution to obtain a perovskite precursor solution, S2. Spin coating the perovskite precursor solution, heating and annealing to obtain the perovskite layer.

8. The preparation method according to claim 7, characterized in that: The ratio of the total mass of active components in the perovskite precursor solution to the mass of hydrazinophenylphosphorous acid is (1100-1150): (0.1-0.3).

9. The preparation method according to claim 7, characterized in that: In the step S2, the rotation speed of the spin coating is 3500-4500 rpm.

10. Use of the perovskite solar cell according to claim 5 or 6 in preparing photovoltaic power generation equipment.

Citation Information

Patent Citations

  • Perovskite thin film based on phosphate group small molecules, preparation method of perovskite thin film and application of perovskite thin film to photovoltaic cell

    CN116056531A

  • Tin-based perovskite thin film, preparation method thereof and device

    CN116322254A

  • Phenylhydrazine-based multifunctional molecular additive for perovskite solar cell and preparation method and application thereof

    CN118084717A